2016
DOI: 10.1016/j.marchem.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and precise analysis of rare earth elements in small volumes of seawater - Method and intercomparison

Abstract: Rare earth elements (REEs) are used as tracers for oceanic trace element cycling. However, the low (picomolar level) dissolved REE concentrations and time-consuming methods have so far hindered their extensive use in marine studies. This study reports the first application of the automated seaFAST-pico system (Elemental Scientific Inc.) in offline mode and using multi-element isotope dilution inductively coupled plasma-mass spectrometry (ID ICP-MS) for the robust and rapid pre-concentration, purification, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
6
34
0
Order By: Relevance
“…In each REE measurement session, we adjust the gas flows to an optimal state to obtain the minimum oxide formation (0.0066 ± 0.0017, 1σ, for the Pr monitor solution) so that the oxide correction is extremely small. Our high-quality data for natural samples used for international calibration (Behrens et al, 2016;Pahnke et al, 2012; agree very well with results from different research groups in the world (section 5). In addition, the repeated analysis of samples yields very good long-term external reproducibility (section 5).…”
Section: 1029/2020gc009042supporting
confidence: 85%
“…In each REE measurement session, we adjust the gas flows to an optimal state to obtain the minimum oxide formation (0.0066 ± 0.0017, 1σ, for the Pr monitor solution) so that the oxide correction is extremely small. Our high-quality data for natural samples used for international calibration (Behrens et al, 2016;Pahnke et al, 2012; agree very well with results from different research groups in the world (section 5). In addition, the repeated analysis of samples yields very good long-term external reproducibility (section 5).…”
Section: 1029/2020gc009042supporting
confidence: 85%
“…The method is intercalibrated with three other laboratories and agrees within analytical uncertainty with the intercalibration results from BATS (Pahnke et al, 2012;Behrens et al, 2016). The external reproducibility of the data presented here is <4% (RSD) except for La (5%) and Ce (8%).…”
Section: Methodssupporting
confidence: 71%
“…Rare earth elements concentrations were measured at the University of Oldenburg using an offline seaFAST isotope dilution ICP-MS method described in Behrens et al (2016). The method is intercalibrated with three other laboratories and agrees within analytical uncertainty with the intercalibration results from BATS (Pahnke et al, 2012;Behrens et al, 2016).…”
Section: Methodsmentioning
confidence: 89%
“…The importance of the monoisotopic element concentrations for quantifying the behavior of the 'anomalous' elements was enlightened when more LA data for seawater and hydrogenous sediments became available [116]. Utilizing multi-element isotope dilution inductively coupled plasma-mass spectrometry (ID ICP-MS), Behrens et al [117] reported the first application of the automated seaFAST-pico system in the offline mode for rapid and robust purification, pre-concentration, and analysis of dissolved LAs from small volumes (11 to 12 ml) of seawater. In extraction techniques (either solid phase extraction or liquid-liquid extraction), samples are exposed to other reagents, making it quite challenging to maintain process blanks below the levels required to quantify the LA accurately [118].…”
Section: Gd Determination In the Aqueous Environmentmentioning
confidence: 99%